Cobalt-exchanged natural zeolite catalysts for catalytic oxidation of phenolic contaminants in aqueous solutions. (August 2016) - Saputra, Edy; Budihardjo, Mochamad Arief; Bahri, Syaiful; Pinem, Jhon Armedi
Abstract: Indonesia (IZ) and Australia (AZ) natural zeolites were employed to prepare cobalt exchanged catalysts. Characterization tests of scanning electron microscopy (SEM), X-ray diffraction (XRD) and Brunaeuer-Emmet-Teller (BET) were used for performing sample analyses. The efficiencies of phenol removal on the catalysts were evaluated by the catalytic oxidation of phenol with sulfate radicals. Cobalt-exchanged catalysts showed higher phenol removal efficiencies than adsorption, Oxone self-oxidation and unmodified zeolites. The reactions were observed to be more efficiently described by the zero-order kinetics, while the respective Co/IZ and Co/AZ activation energies were 44.1 and 59.5. This study provides a novel application of low-cost natural zeolites for environmental remediation.